IMPLEMENTASI MENGURANGI CACAT PADA PRODUK HOUSING VANE DI AREA SELECTION PT. SUMIDEN SINTERED COMPONENTS INDONESIA MENGGUNAKAN METODE STATISTICAL QUALITY CONTROL (SQC) - Yusita Attaqwa; Soleh Nurkholik (Fakultas Teknik dan Rekayasa, 2024)
One of the main factors that determines a company's performance is producing high quality products. In order to achieve this goal, a good strategy must be implemented, one of which is paying attention to and maintaining the quality of the products produced so that they can meet consumer needs. The research aims to analyze defective products in vane housing products at PT. Sumiden Sintered Components Indonesia. The research I conducted used the Statistical Quality Control (SQC) method. So the problem formulation in this research is to identify and analyze what factors cause housing vane products to experience these defects. So what improvements can be implemented to improve the quality of the housing vane product? The sample collection method uses a check sheet tool to determine the level of success of the research carried out. The analysis model is to compare data on a fishbone diagram before and after implementation. The results obtained in this research are reducing products that should be thrown away into products that can be reprocessed and reducing company losses.